Dripping dynamics from a tilted nozzle / Amaraja Taur - Amaraja, Taur (2014)
The dripping dynamics of Newtonian liquids emanating from a tilted nozzle is studied. A high speed camera is employed to observe the drop breakup process. The level of viscosity, flow rate, nozzle diameter, and nozzle inclination angle had been varied independently. The drop break up time tb, which is the time interval between two subsequent drops, and the different modes of dripping have been identified. The new experiments reveal that increasing the nozzle inclination angle results in lowering the drop breakup times for all viscosities and nozzle diameters investigated, suggesting that the surface tension forces cannot hold the drops longer despite the weakened effective gravitational pull. This counter-intuitive finding is further corroborated by pendant drop experiments and computations. In the modes of dripping, as the liquid flow rate increases, the system transitions from period-1(P1) dripping to limit cycle (LC) before showing chaotic (C) responses. A phase diagram showing the transition between the different dripping modes for different nozzle inclination angle is constructed in the (We, Ka) space, where We (Weber number) measures the relative importance of inertia to surface tension force and Ka (Kapitza number) measures the relative importance of viscous to surface tension forces. At low values of We and Ka, the system shows a transition from period-1 to limit cycle before chaos. The limit cycle region narrows down with increase in inclination. Further increase in the values of We and Ka gives a direct transition from period-1 to chaos. The experimental volumes of primary drops by image analysis show good agreement with the volumes obtained from the correlation developed, showing a maximum of 15% error. The experimental data obtained from image analysis further suggest that, in the P1 regime the pendant drop volume varies such that the trend of the primary drop volume differs significantly from that of the breakup time.